Aquaporin 11, a regulator of water efflux at retinal Müller glial cell surface decreases concomitant with immune-mediated gliosis. Issue 1 (December 2016) - Deeg, Cornelia; Amann, Barbara; Lutz, Konstantin; Hirmer, Sieglinde; Lutterberg, Karina; Kremmer, Elisabeth; Hauck, Stefanie
Abstract Background Müller glial cells are important regulators of physiological function of retina. In a model disease of retinal inflammation and spontaneous recurrent uveitis in horses (ERU), we could show that retinal Müller glial cells significantly change potassium and water channel protein expression during autoimmune pathogenesis. The most significantly changed channel protein in neuroinflammatory ERU was aquaporin 11 (AQP11). Aquaporins (AQP, 13 members) are important regulators of water and small solute transport through membranes. AQP11 is an unorthodox member of this family and was assigned to a third group of AQPs because of its difference in amino acid sequence (conserved sequence is only 11 %) and especially its largely unknown function. Methods In order to gain insight into the distribution, localization, and function of AQP11 in the retina, we first developed a novel monoclonal antibody for AQP11 enabling quantification, localization, and functional studies. Results In the horse retina, AQP11 was exclusively expressed at Müller glial cell membranes. In uveitic condition, AQP11 disappeared from gliotic Müller cells concomitant with glutamine synthase. Since function of AQP11 is still under debate, we assessed the impact of AQP11 channel on cell volume regulation of primary Müller glial cells under different osmotic conditions. We conclude a concomitant role for AQP11 with AQP4 in water efflux from these glial cells, which is disturbed in ERU. This could probably contribute to swelling and subsequent severe complication of retinal edema through impaired intracellular fluid regulation. Conclusions Therefore, AQP11 is important for physiological Müller glia function and the expression pattern and function of this water channel seems to have distinct functions in central nervous system. The significant reduction in neuroinflammation points to a crucial role in pathogenesis of autoimmune uveitis.